Elasticity of Travel Time and Travel Cost of Private Vehicles and Public Transportation in Bandung, Indonesia - Elshaan Helmmie; Tri Basuki Joewono (Institute of Research and Community Outreach - Petra Christian University, 2022)
Understanding mechanism of users in responding determinant variables to use mode of transport is beneficial to anticipate the effect of policy. This study aims to identify the elasticity value of travel time and travel cost of the users of private vehicles and public transportation. Using data from users of private vehicles and public transport in Bandung, Indonesia, the elasticity of travel time and travel cost was calculated based on estimated multinomial logit model (MNL) logit. The elasticity was calculated based on gasoline prices, parking fees, transfer fees, access times, travel times, and waiting times. Based on the results of the elasticity values for travel attribute, it was found that in access time and travel time, Trans Metro Bandung (TMB) Bus had the largest elasticity of -0,564 and -5,001, respectively, so TMB Bus was the most sensitive to changes in access time and travel time. In terms of waiting times and fixed costs/gasoline, conventional taxi has the highest elasticity values of -2,630 and -1,604, respectively, so conventional taxi is the most sensitive to changes in waiting time and fixed costs/gasoline.